2002
DOI: 10.1016/s0006-3495(02)73898-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Investigation of Membrane-Bound Bundles of the Channel-Forming Transmembrane Domain of Viral Protein U from the Human Immunodeficiency Virus HIV-1

Abstract: Molecular dynamics (MD) simulations have been carried out on bundles of the channel-forming transmembrane (TM) domain of the viral protein U (VPU(1-27) and VPU(6-27)) from the human immunodeficiency virus (HIV-1). Simulations of hexameric and pentameric bundles of VPU(6-27) in an octane/water membrane mimetic system suggested that the pentamer is the preferred oligomer. Accordingly, an unconstrained pentameric helix bundle of VPU(1-27) was then placed in a hydrated palmitoyl-oleyl-3-n-glycero-phosphatidylethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 25 publications
7
47
0
Order By: Relevance
“…The calculated structure (Fig. 2B) agrees fairly well with that derived from Molecular Dynamics simulations (21,22). Significantly, it assigns the location of Trp-22 and Ser-23 at proposed strategic positions for the gating of the channel.…”
Section: Tasp Vpu Proteins and The Oligomeric State Of The Conduc-supporting
confidence: 78%
“…The calculated structure (Fig. 2B) agrees fairly well with that derived from Molecular Dynamics simulations (21,22). Significantly, it assigns the location of Trp-22 and Ser-23 at proposed strategic positions for the gating of the channel.…”
Section: Tasp Vpu Proteins and The Oligomeric State Of The Conduc-supporting
confidence: 78%
“…28 Similar stability is then expected for our model in Figure 13(d). Lopez et al carried out molecular dynamics simulations for a Vpu TM pentamer with allatom representations of the phospholipid bilayer and aqueous layers, 26 starting with helix orientations similar to those in Figure 13(d). Although the fivefold symmetry of the pentamer was lost as the simulations proceeded, the helix orientations were generally preserved, again supporting the stability of such pentamer structures.…”
Section: Discussionmentioning
confidence: 99%
“…The goal was simply to generate well-packed oligomer models with the full range of possible s and q angles for comparison with experimental data, not to predict the structures or other properties of Vpu TM oligomers by molecular dynamics simulations in a realistic bilayer environment, as has been done previously (without direct experimental constraints) by other groups. 10,26,[30][31][32] Our approach to modeling and data analysis is similar to the approach used by Kukol and Arkin to interpret Fourier-transform infrared (FTIR) measurements on Vpu TM oligomers. 16 In our modeling procedure, oligomers with a right-handed twist about the symmetry axis have positive s, whereas those with left-handed twist have negative s. With q ¼ 0 , C a sites of I8, I15, and W22 are in the central pore of the oligomer, whereas C a sites of V13, V20, and I27 are on the outside, nearly diametrically opposite to the symmetry axis.…”
Section: Oligomer Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion channel is formed by the homo-oligomers of four to seven helices. Computational studies have suggested that the most probable oligomeric state is a pentamer [46,47]. However, a recent study suggested that there might be more than one possible oligomeric state [9], and the exact state is yet to be determined.…”
Section: Vputmmentioning
confidence: 99%